Emotionally engaging customers in the digital age: the case study of "Burberry love". Issue 3 (11th July 2016) - Straker, Karla; Wrigley, Cara
Abstract : Purpose: – The purpose of this paper is to investigate how companies can design digital channels to evoke desired emotions. Design/methodology/approach: – The successful business case of retailer Burberry has been examined to understand the strategy and customer engagement of digital channels implemented by decoding the emotional intensions. Findings: – Results illustrate that the ability to create engaging interactions via digital channels with customers has a significant impact on growth, revenue and brand advocacy. Findings from this study provide a new empirical support for the proposition that emotions can be utilised to guide company digital strategy for building digital channel relationships with customers. Originality/value: – This is the first study to examine the relationship between digital channels, emotion and customer responses to digital engagements. The inclusion of an emerging theory model is outlined to explain the successful process of reformulating business strategy through a dynamic and creative process of intersecting emotion, strategy and digital channels.